An unusual case of corneal perforation secondary to Frontal Bone Mucormycosis - Venugopal Anitha; Maneksha Velu; Senthil Babu; Arasi Rajesh; Meenakshi Ravindran (Oman Journal of Ophthalmology)
We present the case of a 52-year-old male with a complex clinical presentation involving frontal sinus osteomyelitis (OM), mechanical ptosis, and extrusion of frontal bone sequestrum under the upper lid skin. He gave a history of chronic sinusitis, an uncontrolled diabetic for the past 2 years. The patient had a history of chronic sinusitis and poorly controlled diabetes for the past 2 years. Histopathological examination of excised sequestrum, stained with hematoxylin and eosin, confirmed a diagnosis of mucormycosis. Anterior segment examination revealed a corneal melt with a shallow anterior chamber. Initial management included the application of an amniotic membrane to promote epithelization. This is the first reported case of frontal bone OM leading to corneal melt, attributed to the mechanical erosion caused by the sequestered bone impinging on the corneal surface.